Live poultry vaccines against highly pathogenic avian influenza viruses - Elizaveta Boravleva; Alexandra Gambaryan (Microbiology Independent Research Journal, 2018)
The widespread circulation of highly pathogenic avian influenza viruses (HPAIVs) and their occasional transmission to humans creates a constant pandemic threat and leads to significant economic losses in the poultry industry. The development of an effective and safe vaccine for the broad protection of poultry from H5N1 HPAIVs remains an important goal. Prevention of the virus transmission between ducks and chickens is important for the efficient control of the spread of avian influenza. The oral administration of live vaccines corresponds to the natural route of infection that leads to virus replication in the intestinal epithelial cells that cause a well-balanced and broad immune response providing protection against the viruses of distant clades. The broad protection is the important advantage of live-attenuated influenza vaccines when compared to inactivated ones. Here, we give an overview of the latest approaches and results in the development of live poultry vaccine candidates against HPAIVs.